PERBANDINGAN PRESTASI BELAJAR FISIKA ANTARA SISWA YANG AKTIF DALAM EKSTRAKURIKULER PRAMUKA DENGAN PADUAN SUARA - H. A, Nurfitriana; Siahaan, Betty Zelda; Rustana, Cecep E. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The purpose of this study was to compare the student achievement in physics between students who are active in scout extracurricular with the choir extracurricular. This research was held in SMAN 39 Jakarta Timur in June 2015. The research sample consisted of 15 students of class XI MIA who follow scout extracurricular (X1) and 15 students of class XI MIA who follow choir extracurricular (X2). The method used is the Ex Post Facto. The instrument used was a questionnaire of students who active in scout extracurricular and choir extracurricular, amounting to 26 the questions and scores of student achievement in physics first semester of school year 2014-2015. Prerequisite test using test of normality and homogeneity test. Hypothesis test with t test with criteria Ho accepted if -ttabel ≤ tcount ≤ ttabel at significance level of 5% with df = n1 + n2 - 2 RESULTS: Student achievement in physics KI 3 X1 and X2 are -1,701≤ -1.61 ≤ 1.701 then Ho is accepted; Student achievement in physics KI 4 X1 and X2 are ≤ 1.701 -1.701 -0.29 ≤ then Ho is accepted; Student achievement in physics KI 1 & 2 X1 and X2 at a significance level of 5% and df = n - 1 = 14 was -1.76 ≤ 0.49 ≤ 1.76 then Ho is accepted or there are no differences in student achievement in physics between students who are active in scout extracurricular with students who are active in choir extracurricular. Keywords: student achievement, scout extracurricular, choir extracurricular.